Utilization of saluyot (Corchorus olitorius Linn.) leaves in fettucine pasta - Roscom, Kristine Karen Amar; Quijano, Ana Marie M. (1997)
The attempt to increase vitamin A in fettucine pasta was done by incorporating different levels of pureed saluyot leaves which is high in beta-carotene content. The optimum level of incorporation of saluyot leaves puree into the fettucine pasta was found to be 16% based on descriptive characteristics, acceptability ratings of the product attributes such as color, odor, texture, flavor, mouthfeel and general product acceptability. From the determination of upscaling efficiency, a 2 kg saluyot fettucine pasta was found to have a higher acceptability in terms of texture, mouthfeel and panelist's attitude towards the product compared to a 500 g laboratory production but with lower percentage product yield. Specifications and critical control points were established based on the upscale production. Another 2 kg upscale production of air-dried pasta was found to be significantly different only in color compared to the cabinet-dried pasta. Vitamin A of the cabinet dried product was obtained to be 54.7 RE and 109.4 ug beta-carotene which provides for 10% and 12% of RDA for male and female respectively making it a good source vitamin A. Dietary fiber increased to 0.26 g/100g compared to macaroni pasta with 0.03 g/100g. Calculated selling price of the dried pasta fettucine was P52.70/500 g.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Vegetables -- Philippines; Saluyot